Predictors of functional capacity and skill in youth soccer players - Figueiredo, A. J.; Coelho e Silva, M. J.; Malina, R. M. (Scandinavian Journal of Medicine & Science in Sports, 2011)
Predictors of functional capacities and skills in 143 soccer players aged 11-14 years from five clubs in Portugal were investigated. Data for players aged 11-12 (n=75) and 13-14 (n=68) years included chronological age, skeletal age, stage of pubic hair (PH), anthropometry, four functional capacities, four soccer skills and experience; composite functional and skill scores were derived. Multiple linear regression analysis was used to examine the independent effects of age, maturity, body size and proportions, adiposity and experience on individual functional capacities and skills and composite scores. Explained variances differed among functional capacities (22-48%) and skills (<25%), and were greater for composite functional (younger 37%, older 58%) than skill (younger 26%, older 18%) scores. Skeletal maturity was a predictor of the counter-movement jump in both groups and of composite functional and skill scores in older players. Age and adiposity were primary predictors in players aged 11-12 years, while experience and a proportionally longer trunk (conversely, relatively shorter lower extremities) appeared among predictors in players aged 13-14 years. PH was not among predictors. Except for the counter-movement jump, predictors of functional capacities and soccer skills differed between age groups.